The Role of Classroom Teachers in the Development of the Independent Curriculum in Primary Schools - Efendi, Arfan; Zaini, Zainuddin Al Haj; Machfudi, Moch. Imam (EDUTEC : Journal of Education And Technology, 2025)
Teachers are not only responsible for teaching but also play an active role in curriculum development to ensure effective implementation in classrooms. This study aims to examine the implementation of the Independent Curriculum at Al Baitul Amien 02 Elementary School (Full Day School) in Jember, focusing on the role of fourth-grade teachers. A qualitative approach was employed, utilizing interviews, observations, and document studies as data sources. The findings revealed three main issues: limited training and experience with the Independent Curriculum, insufficient high-quality references in textbooks, and suboptimal time management. Additionally, disparities in digital access and teachers' technological competencies pose challenges to fostering creative and innovative learning. This study highlights that active teacher involvement in curriculum development and adaptation can enhance learning quality, though it requires greater support in training and resources. The study provides insights for improving the implementation of the Independent Curriculum in primary school settings.